Acute Flaccid Myelitis in Children in Zhejiang Province, China - Gong, Liming; Wang, Yilong; Zhang, Weiqing; Chen, Chen; Yang, Xinghui; Xu, Lu; Zhao, Congying; Jiang, Lihua; Yuan, Zhefeng; Xia, Zhezhi; Jiang, Peifang; Ge, Qiong; et al. (Frontiers in Neurology, 2020)
In July–December 2018, an outbreak of polio-like acute flaccid myelitis (AFM) occurred in Zhejiang province, China. enterovirus (EV)-D68 infection has been reported to be associated with AFM. This study aimed to investigate the clinical presentation, laboratory findings, and outcomes of AFM patients. We investigated the clinical and virologic information regarding the AFM patients, and real-time PCR, sequencing, and phylogenetic analysis were used to investigate the cause of AFM. 18 cases met the definition of AFM, with a median age of 4.05 years (range, 0.9–9 years) and nine (50%) were EV-D68 positive. Symptoms included acute flaccid limb weakness and cranial nerve dysfunction. On magnetic resonance imaging, 11 (61.1%) patients had spinal grey matter abnormalities, Electromyography results of 16 out of 17 patients (94.1%) were abnormal. Cerebrospinal fluid (CSF) pleocytosis was common (94.4%), while CSF protein concentration was normal in all patients. There was little improvement after early aggressive therapy. Phylogenetic analysis revealed that EV-D68 subclade B3 was the predominant lineage circulating in Zhejiang province in 2018. More effort needed to determine the full association between EV-D68 and AFM and to develop novel preventive and therapeutic measures.